New Applications of HBOC-201: A 25-Year Review of the Literature - Cao, Min; Zhao, Yong; He, Hongli; Yue, Ruiming; Pan, Lingai; Hu, Huan; Ren, Yingjie; Qin, Qin; Yi, Xueliang; Yin, Tao; Ma, Lina; Zhang, Dingding; et al. (Frontiers in Medicine, 2021)
If not cured promptly, tissue ischemia and hypoxia can cause serious consequences or even threaten the patient's life. HBOC-201, bovine hemoglobin polymerized by glutaraldehyde and stored in a modified Ringer's lactic acid solution, has been investigated as a blood substitute for clinical use. HBOC-201 was approved in South Africa in 2001 to treat patients with low Hb levels when RBCs are contraindicated, rejected, or unavailable. By promoting oxygen diffusion and convective oxygen delivery, HBOC-201 may act as a direct oxygen donor and increase oxygen transfer between RBCs and between RBCs and tissues. Therefore, HBOC-201 is gradually finding applications in treating various ischemic and hypoxic diseases, including traumatic hemorrhagic shock, hemolysis, myocardial infarction, cardiopulmonary bypass, perioperative period, organ transplantation, etc. However, side effects such as vasoconstriction and elevated methemoglobin caused by HBOC-201 are major concerns in clinical applications because Hbs are not encapsulated by cell membranes. This review summarizes preclinical and clinical studies of HBOC-201 applied in various clinical scenarios, outlines the relevant mechanisms, highlights potential side effects and solutions, and discusses the application prospects. Randomized trials with large samples need to be further studied to better validate the efficacy and safety of HBOC-201 to the extent where patient-specific treatment strategies would be developed for various clinical scenarios to improve clinical outcomes.